Interspecific Divergence of Two Sinalliaria (Brassicaceae) Species in Eastern China - Lei Zhang; Tingting Zeng; Huan Hu; Liqiang Fan; Honglei Zheng; Quanjun Hu (Frontiers in Plant Science, 2018)
How endemic species originated in eastern Asia has interested botanists for a long time. In this study, we combined experimental and computational modeling approaches to examine the morphological and genetic divergence and reproductive isolation of two tentative species of Sinalliaria (Brassicaceae) endemic to eastern China, S. limprichtiana and S. grandifolia. Most of the examined morphological characters (including hairs of leaf blades and stems, corolla length and width, and flower stalk length) were well-delineated between two species at the same ploidy level, and there was clear evidence of reproductive isolation between them (mainly due to post-pollination barriers) in the common garden environment. There were also strong and consistent divergences in the population genetic data. Coalescent simulations based on sequence variation of the nuclear genes suggest that interspecific divergence began during the Pleistocene when the climate oscillated in eastern Asia. Gene flow between two species appears to have been very limited and asymmetrical. Our results suggested that both species are well-differentiated and that the fast divergence between them might have been together shaped by both stochastic processes and habitat selection pressures.